An Adolescent Sensitive Period for Social Dominance Hierarchy Plasticity Is Regulated by Cortical Plasticity Modulators in Mice - Bicks, Lucy K.; Peng, Michelle; Taub, Alana; Akbarian, Schahram; Morishita, Hirofumi (Frontiers in Neural Circuits, 2021)
Social dominance hierarchies are a common adaptation to group living and exist across a broad range of the animal kingdom. Social dominance is known to rely on the prefrontal cortex (PFC), a brain region that shows a protracted developmental trajectory in mice. However, it is unknown to what extent the social dominance hierarchy is plastic across postnatal development and how it is regulated. Here we identified a sensitive period for experience-dependent social dominance plasticity in adolescent male mice, which is regulated by mechanisms that affect cortical plasticity. We show that social dominance hierarchies in male mice are already formed at weaning and are highly stable into adulthood. However, one experience of forced losing significantly reduces social dominance during the adolescent period but not in adulthood, suggesting adolescence as a sensitive period for experience-dependent social dominance plasticity. Notably, robust adolescent plasticity can be prolonged into adulthood by genetic deletion of Lynx1, a molecular brake that normally limits cortical plasticity through modulation of cortical nicotinic signaling. This plasticity is associated with increased activation of established nodes of the social dominance network including dorsal medial PFC and medial dorsal thalamus evidenced by increased c-Fos. Pharmacologically-mediated elevation of cortical plasticity by valproic acid rapidly destabilizes the hierarchy of adult wildtype animals. These findings provide insight into mechanisms through which increased behavioral plasticity may be achieved to improve therapeutic recovery from psychiatric disorders that are associated with social deficits.